Development of a Human Resource Readiness Framework Model Based on Innovative Leadership on Organizational Culture on The Performance of MSMEs Mediating Role Work Motivation - Hadi, Dita Eka Putri; Prayogonegoro, Prabu Nurdin; Sudarmiatin, Sudarmiatin; Wijijayanti, Trisetia (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
Balikpapan City, as one of the economic centers in East Kalimantan, plays an important role in the development of Micro, Small, and Medium Enterprises (MSMEs). The Goetji, as one of the MSMEs engaged in the beverage industry, faces significant challenges and opportunities in improving its performance and competitiveness. This study aims to analyze the influence of employee work motivation, corporate culture, and corporate atmosphere on business production and economic growth in Balikpapan City. The research method used is a quantitative approach with statistical analysis to measure the relationship between the variables studied. Data was collected through a survey involving The Goetji employees and analyzed using regression analysis to identify the significance of each factor's influence. The results show that employee motivation has a significant effect on the development of The Goetji SMEs, with a significance value of 0.000, indicating a strong relationship. In addition, a positive corporate culture and a supportive corporate atmosphere also contribute to increased productivity and product quality. This positive impact is not only seen in The Goetji's internal performance but also contributes to local economic growth by creating jobs and increasing regional income. This study concludes that strengthening work motivation and a positive corporate culture are key to improving the performance of MSMEs, which in turn contributes to the economic growth of Balikpapan City. Recommendations are provided to continue developing strategies that support these two aspects in order to achieve greater sustainability and growth